2010
DOI: 10.1007/s12640-010-9180-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hydrogen Sulfide Generation Contributes to 1-Methy-4-Phenylpyridinium Ion-Induced Neurotoxicity

Abstract: Reactive oxygen species (ROS) overproduction contributes to the neurotoxicity of 1-methy-4-phenylpyridinium ion (MPP(+)). Increasing studies have shown that hydrogen sulfide (H(2)S) is an endogenous antioxidant gas. We have hypothesized that MPP(+)-caused neurotoxicity may involve the imbalance of proportion to this endogenous protective antioxidant gas. The aim of this study is to evaluate whether MPP(+) disturbs H(2)S synthesis in PC12 cells, a clonal rat pheochromocytoma cell line, and whether disturbance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
(48 reference statements)
5
24
1
Order By: Relevance
“…-induced cytotoxcity and apoptosis in PC12 cells [7] and that inhibition of H 2 S by MPP ? is responsible for its neurotoxicity [19]. The present work shows that treatment of PC12 cells with It has been demonstrated that ROS play a central role in MPP ?…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…-induced cytotoxcity and apoptosis in PC12 cells [7] and that inhibition of H 2 S by MPP ? is responsible for its neurotoxicity [19]. The present work shows that treatment of PC12 cells with It has been demonstrated that ROS play a central role in MPP ?…”
Section: Discussionsupporting
confidence: 52%
“…We have found that PC12 cells generate H 2 S by cystathionine-b-synthetase (CBS), not by cystathionine-c-lyase (CSE) [19]. Thus, knockdown of CBS in PC12 cells was accomplished using shRNA CBS (the shRNA target sequences is TGACCAGGCACCTGTGGTCAACGAGTC TG).…”
Section: Rna Interference (Rnai)mentioning
confidence: 99%
See 3 more Smart Citations